Investigation of Apple Scum and Its Modification with Magnesium Chloride and Hydrogen Peroxide for Removal of Toxic Hexavalent Chromium from Aqueous Solution - M. Noori Sepehr; M. Taghavi; M. Zarrabi (Bihdād, 2014)
Introduction: Chromium is one of the heavy metals present in effluents produced from industrial activities and exists in the trivalent and hexavalent state. It is mentioned that hexavalent chromium has is more hazardous due to its carcinogenic properties. Due to its hazard, Cr(VI) must be removed from wastewaters prior discharge into the environment. For this reason, the present aimed for removal of hexavalent chromium by Apple Scum and its modification with magnesium chloride and hydrogen peroxide. Material and Methods: Apple Scum was obtained from Galin Plan as waste materials. The Apple Scum was modified with 2M MgCl2 and 30% H2O2. Several experimental parameters such as solution pH (1-9), contact time (1-100 min), solution temperature (20-60oC), adsorbent dosage (2-10 g/L) and initial chromium concentration (10-100 mg/L) was investigated. All experiments were done in batch system. Results: The results of present work reveals that chromium removal efficiency was increased with increase in adsorbent dosage, contact time and initial chromium concentration, while decreased for increase in solution pH and temperature. Higher removal efficiency was observed at pH 1, 100 min contact time, 100 mg/L chromium concentration and 20oC temperature. At this optimal condition up to 90% of chromium was removed. In addition, the modification of Apple Scum leads to increase in chromium removal efficiency up to 98% for MgCl2 modified adsorbent and up to 95% forH2O2 modified one. Conclusion: The results of present work well demonstrate the waste Apple Scum for removal of hexavalent chromium and its sorption capacity will be improved in the case of modification with H2O2 and MgCl2.